2011
DOI: 10.1002/aic.12595
|View full text |Cite
|
Sign up to set email alerts
|

An iterative method for design of water‐using networks with regeneration recycling

Abstract: in Wiley Online Library (wileyonlinelibrary.com).Both freshwater consumption and wastewater discharge can be reduced significantly when wastewater regeneration recycling is introduced in the design of the water-using networks (WUNs). However, it is often difficult to design the WUNs involving regeneration recycling. This article presents an iterative method to design the WUNs involving regeneration recycling. The final designs can be obtained without iteration for the networks with known regenerated concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…The results are the same as that obtained by the method of Pan et al (2012). However, no detailed iterative calculations are required to obtain the above values with the method proposed in this paper.…”
Section: Case Studiesmentioning
confidence: 51%
See 4 more Smart Citations
“…The results are the same as that obtained by the method of Pan et al (2012). However, no detailed iterative calculations are required to obtain the above values with the method proposed in this paper.…”
Section: Case Studiesmentioning
confidence: 51%
“…We can obtain C max R;A from the above equation, and obtain C R;A with the method of Pan et al (2012), as shown in Table 4. It can be seen from Table 4 that C R;A are lower than C max R;A across the regenerated concentration interval [8.39, 20] ppm of contaminant B.…”
Section: Case Studiesmentioning
confidence: 99%
See 3 more Smart Citations